Melioidosis in Southern Vietnam: clinical surveillance and environmental sampling. - Parry, C; Wuthiekanun, V; Hoa, N; Diep, T; Thao, LT; Loc, P; Wills, B; Wain, J; Hien, T; White, N; Farrar, J (1999)
From 1992-1998, Burkholderia pseudomallei was isolated from only 9 (0.25%) of 3653 cultures of blood from febrile patients admitted to the Centre for Tropical Diseases in Ho Chi Minh City, an infectious disease referral center for southern Vietnam. Soil was sampled from 407 sites in 147 rice fields along the 5 major roads radiating from Ho Chi Minh City. B. pseudomallei was isolated from 73 sites (18%) in 39 rice fields (27%), but only 15 (21%) of the 71 isolates from 9 (6%) of 147 fields were the virulent l-arabinose (ara)-negative biotype. All except 1 of the fields with the ara-negative biotype were close to the homes of the patients with melioidosis. The low incidence of melioidosis in the provinces around Ho Chi Minh City may be explained by the restricted distribution of ara-negative B. pseudomallei in the soil in this area.